2017
DOI: 10.1073/pnas.1703879114
|View full text |Cite
|
Sign up to set email alerts
|

Protein-mediated viral latency is a novel mechanism for Merkel cell polyomavirus persistence

Abstract: Viral latency, in which a virus genome does not replicate independently of the host cell genome and produces no infectious particles, is required for long-term virus persistence. There is no known latency mechanism for chronic small DNA virus infections. Merkel cell polyomavirus (MCV) causes an aggressive skin cancer after prolonged infection and requires an active large T (LT) phosphoprotein helicase to replicate. We show that evolutionarily conserved MCV LT phosphorylation sites are constitutively recognized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
123
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(133 citation statements)
references
References 50 publications
10
123
0
Order By: Relevance
“…However, 500 ng of LT expression plasmid reduced early and late promoter activities in HDF and early promoter activity in MCC13 cells, but had only a slight or no effect, but significantly stimulated the HUN and MS1 (a 20 and 40% increase, respectively) late promoters. Kwun et al found that MCPyV LT repressed early and late promoter activity of MCPyV isolate MCC339 in HEK293 cells, but they did not examine the effect of LT in MCC13 or HDF cells [42]. Yet, in another study by Ajuh and co-workers, the authors showed that LT trans-activated the MCPyV R17b (= consensus) early and late promoter in HEK293T cells [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 500 ng of LT expression plasmid reduced early and late promoter activities in HDF and early promoter activity in MCC13 cells, but had only a slight or no effect, but significantly stimulated the HUN and MS1 (a 20 and 40% increase, respectively) late promoters. Kwun et al found that MCPyV LT repressed early and late promoter activity of MCPyV isolate MCC339 in HEK293 cells, but they did not examine the effect of LT in MCC13 or HDF cells [42]. Yet, in another study by Ajuh and co-workers, the authors showed that LT trans-activated the MCPyV R17b (= consensus) early and late promoter in HEK293T cells [29].…”
Section: Discussionmentioning
confidence: 99%
“…In these cells, truncated MKL-1 and MS-1 LT inhibited the corresponding early promoter. The reason for the cell-specific effect of truncated LT on the MCPyV promoter is not known, but MCPyV LT has been shown to interact with several cellular factors [42]. Different interaction partners in distinct cell types may determine the effect of LT on the MCPyV promoter activity.…”
Section: Discussionmentioning
confidence: 99%
“…After primary infection, which occurs very early in life, MCPyV seems to remain in a latent/persistent state lifelong in immune competent hosts ( 4 ). The cellular protein SCF E3 ligase, targeting MCPyV LT oncoprotein seems to allow this small DNA tumor virus to remain in the latency state ( 30 ). Our data indicate that MCPyV may persist/reactivate in the host, whereas it can be detected at low prevalence and at low-DNA viral copy in the sera of immunocompetent healthy blood donors.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood monocytes have been proposed to act as a reservoir of infected cells 24 . MCPyV reporter pseudovirus can enter many cell types, including keratinocytes 28 , 29 , although dermal fibroblasts and HEK 293 cells are the only cells in which productive viral infection has been demonstrated in vitro 28 , 30 .…”
Section: Biological Features Of MCCmentioning
confidence: 99%